Partial Purification of Anthocyanins (Brassica oleracea var. Rubra) from Purple Cabbage Using Natural and Modified Clays as Adsorbent - Darlyson Tavares Guimarães; Liana Maria Ramos Mendes; Luiz Bruno de Sousa Sabino; Edy Sousa de Brito; Enrique Vilarrasa-García; Enrique Rodríguez-Castellón; Juan Antonio Cecilia; Ivanildo José da Silva Junior (Adsorption Science & Technology)
This research is aimed at evaluating strategies for the adsorption and recovery of anthocyanins present in purple cabbage using natural and modified clays as adsorbent. In the batch adsorption experiments, the anthocyanin extracts were put in contact with the adsorbents, and different parameters were evaluated to determine the best conditions for their adsorption and recovery. It was noted that the highest levels of adsorption (28.0 mg g-1) occurred using a porous clay heterostructure (PCH) material as adsorbent, with a mass of 25 mg and 120 min of contact. Under the same conditions, the sepiolite only presented an adsorption capacity of 14.0 mg g-1. The desorption results showed that the 60% methanolic solution recovered 60% of the anthocyanins adsorbed on PCH, while the 80% ethanolic solution recovered 35% of those adsorbed on sepiolite. The eluted anthocyanin solutions showed a 98% lower sugar concentration than the crude extract, indicating the low affinity of the adsorbents for sugars. Six types of acylated cyanidins were identified via UPLC-QToF-MSE in the extract, and it was confirmed from the FTIR analyses that the highest affinity of the clays occurred with the anthocyanins that presented more organic acid in their structure. The results show that PCH and sepiolite have high selectivity for anthocyanins and low affinity for the sugars present in the plant extract, facilitating the process of partial purification and application of these pigments.